TOPOLOGICAL FORMULATIONS OF FINGER TIP PATTERNS AMONG THE DOWN'S SYNDROME - M.S.Kamali; Blanka Schaumann; N.Sakhaeyan (Tehran University of Medical Sciences, 1985)
Finger prints of 68 patients with Down's syndrome and 93 controls have been collected and analyzed for topological of formulation of finger tip patterns suggested by Loesch (1975). The results showed that there may be great differences in the dictionary of the finger patterns of the patients and their controls. Mean lunar and radial patterns showed mostly significant differences among the patients and their controls. Exact role of dermatoglyphic topology of finger patterns in Down's syndrome will be found out only after doing many studies in many populations.